REFLECTION ON TECHNOLOGY-ENHANCED LEARNING IN RESEARCH BASED TEACHING METHOD IMPLEMENTATION - Putri, Marisca Revani (Bina Nusantara University, 2020)
The research aimed to investigate the utilization of technological tools in implementing the research-based teaching method in English for Academic Writing Course. The narrative research design was implemented to reach the conclusion of the research. 66 (sixty-six) students enrolled in English for Academic Writing Course were observed. Lecturer?s reflective journal and portfolios were analyzed. An online interview was conducted to confirm the initial findings. There were six technological tools and applications utilized during the preparation process, instruction, and practice process, as well as in the assessment and transfer process. Through a structured reflection process based on Gibbs? model of reflection, the result shows that the students? motivation is increased during the use of technology. Technology also enables students to work collaboratively. Nevertheless, preparation and briefing are needed to be done before the class begins. Like the classic problem of technology implementation, internet access becomes the main challenge in conducting Technology-Enhanced Learning (TEL) in the classroom.